2019
DOI: 10.1080/01402382.2019.1575639
|View full text |Cite
|
Sign up to set email alerts
|

Eurosceptics in trilogue settings: interest formation and contestation in the European Parliament

Abstract: Trilogues have been studied as sites of secluded inter-institutional decision making that gather the Council of the European Union, the European Parliament (EP) and the European Commission. Trilogues, however, are not exempt from formal and informal party-political dynamics that affect intraand inter-institutional contestation. The increase in Eurosceptics in the 2014 EP elections offers an opportunity to investigate their efforts to shape the position and behaviour of the EP negotiating team in trilogues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
(25 reference statements)
2
13
0
Order By: Relevance
“…The ENF and the EFDD (except for the M5S) were systematically excluded from coalitions and their amendments did not survive the preparatory stage. This confirms findings from our previous research, which showed how shadows meetings might give a voice to hard-Eurosceptics but did not offer them an actual chance to influence policy positions (Ripoll Servent & Panning, 2019a;Ripoll Servent & Panning, 2019b). In spite of this, the content analysis reveals the irrelevance of the cordon sanitaire when it comes to excluding far-right and populist voices.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The ENF and the EFDD (except for the M5S) were systematically excluded from coalitions and their amendments did not survive the preparatory stage. This confirms findings from our previous research, which showed how shadows meetings might give a voice to hard-Eurosceptics but did not offer them an actual chance to influence policy positions (Ripoll Servent & Panning, 2019a;Ripoll Servent & Panning, 2019b). In spite of this, the content analysis reveals the irrelevance of the cordon sanitaire when it comes to excluding far-right and populist voices.…”
Section: Resultssupporting
confidence: 86%
“…When it comes to the former, we see a clear use of the cordon sanitaire that allowed mainstream groups to disengage from the ENF and from the non-M5S members of the EFDD. This confirms previous findings that these groups are seen as outcasts and actively isolated by mainstream groups (Ripoll Servent & Panning, 2019a). This strategy does not necessarily respond to the ideological content of their amendments, given that the EPP parroted the anti-immigration and securityled positions of the far-right and populist parties from the ENF and ECR.…”
Section: Qualifications Regulationsupporting
confidence: 87%
See 2 more Smart Citations
“…Second, the cordon sanitaire is still very effective. Mainstream politicians do not want to cooperate with Eurosceptics or let them have any kind of influence (Brack, 2018; Ripoll Servent and Panning, 2019; Startin, 2010). For instance, they have excluded them from any position of responsibility at the beginning of the new parliamentary term: while according to the D’Hondt system in place in the EP, the radical right group should have received two vice-presidencies of the EP as well as two chairmanships of parliamentary committees, the other groups disregarded the informal rules to elect MEPs from other groups to these positions.…”
Section: Discussionmentioning
confidence: 99%